“What is Progressive Librarianship Now?” - Buschman, John (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2025)
A recent book, Contemporary Democratic Theory, is about the decline of democracy. Not an explanation of the phenomenon, but rather a look at how democratic theory has responded. This paper adapts that approach. The context of progressive librarianship (PL) has likewise shifted and consolidated with the results of the 2024 US presidential election and its aftermath. This is not localized or short term, it is global and persistent—and for democracy as well as libraries. The time has come to step back and ask the equivalent questions to that book on democratic theory: what is PL now? How did PL adapt and how might PL adapt? Efforts to document the work of and define PL began in response to “considerable ambiguity about just what constitutes progressive librarianship”—an inquiry conducted over the course of 15 years. It revealed that PL is an umbrella term describing both scholarship and organizational activities, gathering together many labels, if not always comfortably. This paper traces those paths, and based on that history suggests ones for PL to take, and perhaps as important, not to take.